Lateral root development in the maize (Zea mays) lateral rootless1 mutant - Husakova, Eva; Hochholdinger, Frank; Soukup, Ales (Annals of botany, 2013)
BACKGROUND AND AIMS: The maize lrt1 (lateral rootless1) mutant is impaired in its development of lateral roots during early post-embryonic development. The aim of this study was to characterize, in detail, the influences that the mutation exerts on lateral root initiation and the subsequent developments, as well as to describe the behaviour of the entire plant under variable environmental conditions. METHODS: Mutant lrt1 plants were cultivated under different conditions of hydroponics, and in between sheets of moist paper. Cleared whole mounts and anatomical sections were used in combination with both selected staining procedures and histochemical tests to follow root development. Root surface permeability tests and the biochemical quantification of lignin were performed to complement the structural data. KEY RESULTS: The data presented suggest a redefinition of lrt1 function in lateral roots as a promoter of later development; however, neither the complete absence of lateral roots nor the frequency of their initiation is linked to lrt1 function. The developmental effects of lrt1 are under strong environmental influences. Mutant primordia are affected in structure, growth and emergence; and the majority of primordia terminate their growth during this last step, or shortly thereafter. The lateral roots are impaired in the maintenance of the root apical meristem. The primary root shows disturbances in the organization of both epidermal and subepidermal layers. The lrt1-related cell-wall modifications include: lignification in peripheral layers, the deposition of polyphenolic substances and a higher activity of peroxidase. CONCLUSIONS: The present study provides novel insights into the function of the lrt1 gene in root system development. The lrt1 gene participates in the spatial distribution of initiation, but not in its frequency. Later, the development of lateral roots is strongly affected. The effect of the lrt1 mutation is not as obvious in the primary root, with no influences observed on the root apical meristem structure and maintenance; however, development of the epidermis and cortex are impaired.
Keywords: Zea mays; lignin; Plant Epidermis; semenáček; lateral root emergence; životní prostředí; Environment; mutace; kukuřice setá; Hydroponics; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; polyfenoly; hydroponie; Plant Shoots; Gene Expression Regulation, Developmental; Lignin; peroxidase; root apical meristem; kořeny rostlin; Polyphenols; lrt1; epidermis rostlin; rostlinné proteiny; Seedlings; výhonky rostlin; Plant Proteins; buněčná stěna; lateral root; vývojová regulace genové exprese; meristém; Mutation; Plant Roots; Meristem; Cell Wall